Metabolism of Tracer 75Se Selenium From Inorganic and Organic Selenocompounds Into Selenoproteins in Rats, and the Missing 75Se Metabolites - Evenson, Jacqueline K.; Sunde, Roger A. (Frontiers in Nutrition, 2021)
We now know much about selenium (Se) incorporation into selenoproteins, and there is considerable interest in the optimum form of Se for supplementation and prevention of cancer. To study the flux of 75Se into selenoprotein, rats were fed 0 to 5 μg Se/g diet as selenite for 50-80 d, and injected iv with 50 μCi of 75Se-labeled selenite, selenate, selenodiglutathione, selenomethionine, or selenobetaine at tracer levels (~0.5 μg Se), killed at various times, and 75Se incorporation into selenoproteins was assessed by SDS/PAGE. These studies found that there is very rapid Se metabolism from this diverse set of selenocompounds to the common intermediate used for synthesis and incorporation of 75Se into the major selenoproteins in a variety of tissues. No selenocompound was uniquely or preferentially metabolized to provide Se for selenoprotein incorporation. Examination of the SDS/PAGE selenoprotein profiles, however, reveals that synthesis of selenoproteins is only part of the full Se metabolism story. The 75Se missing from the selenoprotein profiles, especially at early timepoints, is likely to be both low-MW and high-MW selenosugars and related precursors, as we recently found in liver of turkeys fed Se-adequate and high-Se diets. Differential metabolism of different selenocompounds into different selenosugar species may occur; these species may be involved in prevention of cancer or other diseases linked to Se status, and may be associated with Se toxicity. Additional studies using HPLC-mass spectroscopy will likely be needed to more fully flesh out the complete metabolism of selenium.